The Economics of Truck Toll Lanes - Andre De Palma; Moez Kilani; Robin Lindsey (European Regional Science Association (ERSA), 2006)
This paper extends an earlier paper by the authors ("Maintenance and congestion pricing with competing roads" presented at ERSA 2005) by introducing two user groups: heavy and light vehicles (viz. trucks and cars). This extension is important since heavy vehicles generate higher congestion and (much) higher pavement damage externalities than do light vehicles. The model features a simple road network with two routes linking a common origin and destination. Pavement quality on each route depreciates with usage and due to natural weathering. Three administration regimes are analysed. The first two regimes are the second best and first best optima. In the second-best regime maintenance levels are chosen for the two routes, but no tolls are applied. In the first-best regime, both maintenance levels and tolls are set to support an optmal division of traffic between the two routes as well as an optimal quality of service. The final regime is a Duopoly. In this regime each route is owned and operated by a different firm that maximises its own profit by choosing a maintenance level and a toll. The analysis (which is still in progress) entails solution and comparison of the outcomes of the three administration regimes. Among other things, we are interested to see in which regimes routes are differentiated so that one route is mainly used by heavy vehicles and the other by light vehicles. Preliminary results suggest that (as in the case of homogeneous users) private ownership is distorted towards excessive tolls and low maintenance effort.
Keywords: 330